Association between syphilis seroprevalence and age among blood donors in Southern China: an observational study from 2014 to 2017. Issue 11 (2nd November 2019) - Wu, Xiaobing; Guan, Yang; Ye, Jianbin; Fu, Hanlin; Zhang, Chunlai; Lan, Lina; Wu, Fengxin; Tang, Fen; Wang, Feng; Cai, Yumao; Yu, Weiye; Feng, Tiejian
Abstract : Objective: This study investigated the association between syphilis seroprevalence and age among blood donors, and described the distribution of serological titres among syphilis-infected donors, aiming to confirm the syphilis epidemic characteristics and to promote effective interventions for older adults. Methods: Data were obtained from the Shenzhen Programme for Syphilis Prevention and Control in 2014–2017. Blood samples were screened using the ELISAs, and confirmed using the Treponema pallidum particle agglutination assay (TPPA) and toluidine red unheated serum test (TRUST). Results: Among 394 792 blood donors, 733 tested TPPA and TRUST positive (active infection), and 728 tested only TPPA positive (historical infection). The overall prevalence of syphilis seropositivity was 370.1 per 100 000 (95% CI 351.1 to 389.0 per 100 000); the prevalence of active infection was 185.7 per 100 000 (95% CI 172.2 to 199.1 per 100 000). People aged ≥45 years displayed a prevalence of 621.8 per 100 000 in syphilis seropositivity and 280.5 per 100 000 in active infection, which were 3.8 times and 2.4 times higher than that for people aged <25 years, respectively. The prevalence of syphilis seropositivity (χ 2 trend =311.9, p trend <0.001) and active infection (χ 2 trend =72.1, p trend <0.001) increased significantly with age. After stratification by gender and year of donation, the increasing trend of prevalence with age remained (p trend <0.05), except for the prevalence of active infection in males and females in 2014. About 16.3% of donors with active infection and aged ≥45 years had a TRUST titre of ≥1∶8, lower than that of patients aged <25 years (51.3%) and 25–34 years (34.1%). Conclusions: The findings confirm the high prevalence of syphilis among older adults, and suggest the need to increase awareness among healthcare providers and deliver more targeted prevention interventions for older adults to promote early testing.